KONSEP DAN URGENSI PENDIDIKAN PANCASILA DAN KEWARGANEGARAAN - Nurul Atikah; Laila Sari; Tya Aryani; Sabrina Nurul Aisyah; Bambang Trisno (JURNAL ILMIAH PENELITIAN MAHASISWA, 2024)
Abstract. Pancasila and citizenship education have a large role in the context of national and state life in Indonesia and the formation and maintenance of a democratic state. Pancasila education is important to be able to educate about moral values, strengthen national identity, the basis for political maturity, safeguard social stability, maintain the sovereignty and integrity of the state, understand the rights and obligations as citizens, strengthen national identity and a sense of belonging to the state, prepare to actively participate in democratic life, foster democratic attitudes, respect for diversity, and support sustainable social and economic development. Thus, Pancasila and citizenship education is not only important for individual interests, but also for the stability, progress and sustainability of the country in the long term. The research method used in this research is a literature study that uses analysis through various sources such as books, journals, articles and other types of documents that support: Research findings show that Pancasila and Citizenship Education is very important to maintain the existing basic values of Indonesian citizens. Even before Pancasila was born, it was to prevent the erosion of these values which could threaten national resilience and sovereignty by liberal values from foreign countries and cultures. Where Pancasila and Citizenship Education is not just a lesson in the world of education, but is also an effort to shape national character and awareness for each individual in building a better Indonesia, maintaining state stability, progress and long-term sustainability of the country.